Determinant Factors of Student's Perception Toward Educational Loan Repayment - Zolkeplee, S. Z.; Hamed, A. B.; Ogunbado, A. F. (Universiti Sains Islam Malaysia, 2024)
The issue of unpayable educational loan that lead to student’s defaults has become a worrying trend all over the world. This research aims to examine the relationship of anxiety, parental influence, media awareness, and religiosity on student’s perception on educational loan repayment. A survey approach has been adopted to investigate student’s perception on educational loan repayment in Universiti Utara Malaysia. The data for this study were collected via structured questionnaires which were completed by 359 undergraduate Muslim’s students who acquire their financial loan from National Higher Education Fund Corporation (NHEFC). The data were then quantitatively analyzed using SPSS program. The findings of Pearson’s correlation showed a positive correlation between student’s perception towards educational loan repayment and religiosity, parental influence, media awareness, and anxiety. Further analysis using a multiple regression indicated that all independent variables explained 32.9 per cent of student’s perception on educational loan repayment. The result again indicated that religiosity and parent’s influence are most influential factors on student’s perception towards educational loan repayment. Whilst, media awareness slightly contributed to student’s perception towards educational loan repayment and anxiety gave no impact. The result implied that the Ministry of Education may design the syllabus in school and university curricular by adding the value of responsibility in loan repayment especially in religious and moral subjects. Besides, the Ministry Education of Malaysia are also urged to use media to disseminate the information regarding the importance for students to make loan repayment to parents as well as students. The collection of student loan then can be used for the next generation in financing their study which could result the prosperity of nation.